2016
DOI: 10.1111/jopy.12240
|View full text |Cite
|
Sign up to set email alerts
|

Lay Conceptions of Volitional Personality Change: From Strategies Pursued to Stories Told

Abstract: Recent research suggests that individuals play an active role in their own personality development. Here, we investigated lay conceptions of this volitional personality change process. In Study 1, participants (N = 602) provided open-ended descriptions of their desired personality changes as well as the strategies they were using to achieve these changes. In Study 2, participants (N = 578) completed these same measures and provided narrative descriptions of the emergence of their desires for (and previous) per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 51 publications
8
68
0
Order By: Relevance
“…As a consequence, the selection of the intervention group may have been driven, in part, by experiencing a discrepancy between the actual personality and levels of personality characteristics, that are seen as desirable by ourselves and by our social environment (Martin et al, 2014b). In general, the current results support the notion that people want to increase in those traits, in which they have lower scores (Baranski et al, 2017;Hudson & Roberts, 2014;Miller et al, 2019) and extends prior research by showing that observers were also able to detect the gap between current and desired traits.…”
Section: Selection Effects For Participation In the Interventionsupporting
confidence: 86%
“…As a consequence, the selection of the intervention group may have been driven, in part, by experiencing a discrepancy between the actual personality and levels of personality characteristics, that are seen as desirable by ourselves and by our social environment (Martin et al, 2014b). In general, the current results support the notion that people want to increase in those traits, in which they have lower scores (Baranski et al, 2017;Hudson & Roberts, 2014;Miller et al, 2019) and extends prior research by showing that observers were also able to detect the gap between current and desired traits.…”
Section: Selection Effects For Participation In the Interventionsupporting
confidence: 86%
“…doi.org/10.15405/epsbs.2018.10.1 Corresponding Author: Natalia Grishina Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 4 the wider context, in particular its relative stability or, on the contrary, significant social transformations, are of great importance for the formation of the relevant human attitudes. This is in part consistent with the results of studies showing that people tend to attribute changes in their lives to external contexts more than their own efforts (Baranksi, Morse, & Dunlop, 2017).…”
Section: Introductionsupporting
confidence: 89%
“…Currently, there is an increase in research, where personal changes are not so much the result of certain events or changes in social roles, but occur due to the active role of an individual (Caspi, Roberts, & Shiner, 2005;Hudson & Fraley, 2015;McCrae et al, 2002). Thus, the problem has moved from the field of clinical studies to the sphere of personality psychology, development and social psychology (Baranksi, Morse, & Dunlop, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of conscientiousness and openness to experience, it is not surprising that becoming more conscientious or more open are common change goals for people. Indeed, research has shown that many people have the desire to change their personality traits (Baranski, Morse, & Dunlop, 2017; Hudson, Fraley, Chopik, & Briley, in press; Hudson & Roberts, 2014; Miller, Baranski, Dunlop, & Ozer, 2019; Robinson, Noftle, Guo, Asadi, & Zhang, 2015). Moreover, the desire to change conscientiousness and openness is not only prevalent among younger adults; older adults also express desires to change their personality (Hudson & Fraley, 2016a; Quintus, Egloff, & Wrzus, 2017).…”
Section: Personality Change Through Interventionmentioning
confidence: 99%